PROMOTING ACTIVE LEARNING BY MEANS OF EFL ONLINE ACTIVITIES - Khalymon, I. Y.; Larina, T. V.; Smelianska, V. V. (Видавництво НДУ ім. М. Гоголя, 2025)
The ongoing crisis in Ukraine has significantly impacted higher education, demanding educators adapt their pedagogy to diverse learning modalities (online, blended, face-to face). Active learning (AL) is crucial for effective student engagement and improved learning outcomes, particularly in online English as a Foreign Language (EFL) instruction, which presents unique challenges like reduced interaction and potential student isolation. While research highlights AL’s benefits, practical guidance for its online implementation in EFL higher education remains limited. This study analyzes existing research on AL, its application in various disciplines (STEM, EFL), and the challenges of online EFL instruction. It explores definitions of AL, its core characteristics, and practical strategies for implementation. The analysis synthesizes key findings from prominent researchers like Lombardi, Yuretich, and Salmon, focusing on student agency, engagement, and knowledge co-construction. The study also examines the design and implementation of e-tivities and discussion forums within Learning Management Systems (LMS) like Moodle, drawing on established frameworks and guidelines. Practical examples of designed e-tivities and discussion forums for pre-service EFL teachers are presented. The study identifies key characteristics of AL, including student agency, active participation, collaborative learning, and metacognition. It highlights effective AL strategies applicable to EFL contexts, such as think-pair-share, group discussions, role-playing, and problem-based learning. The research demonstrates how these strategies can be adapted for online delivery through e-tivities and discussion forums, emphasizing the importance of clear instructions, purposeful tasks, and structured interaction. Specific examples of e-tivities and discussion forums designed for pre-service EFL teachers are provided, showcasing practical applications of the discussed frameworks. These examples integrate various EFL skills (listening, reading, writing, speaking) and promote peer interaction and feedback. This study contributes by providing practical guidance for designing and implementing AL in online EFL higher education, specifically through e-tivities and discussion forums. It synthesizes existing research on AL and adapts it to the unique context of online EFL instruction, offering concrete examples of how to create engaging and effective learning experiences for pre-service teachers. The focus on integrating various EFL skills and fostering peer interaction within online activities is a novel contribution. The findings of this study are directly applicable to EFL instructors in higher education seeking to enhance student engagement and learning outcomes in online and blended learning environments. The provided examples of e-tivities and discussion forums can be readily adapted and implemented in EFL courses. The study’s emphasis on clear guidelines, structured interaction, and purposeful tasks offers valuable insights for designing effective online AL experiences.
Keywords: active learning; online learning; English as a foreign language; e-tivities; discussion forums; higher education; student engagement; teacher and philology training; Moodle